2003
DOI: 10.1046/j.1525-139x.2003.16025.x
|View full text |Cite
|
Sign up to set email alerts
|

THE CLINICAL EPIDEMIOLOGY OF CARDIOVASCULAR DISEASES IN CHRONIC KIDNEY DISEASE: Clinical Epidemiology of Cardiovascular Disease in Chronic Kidney Disease Prior to Dialysis

Abstract: Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality in patients with end-stage renal disease (ESRD). Both in dialysis and in transplant patients, CVD remains the leading cause of death. There is accumulating evidence that the increase in CVD burden is present in patients prior to dialysis, due to both conventional risk factors as well as those specific to kidney disease. Of importance is that even in patients with mild kidney disease, the risk of cardiovascular events and death is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(63 citation statements)
references
References 40 publications
0
61
0
2
Order By: Relevance
“…LVH is generally considered to be associated with hypertension caused by uremia [3]. Nevertheless, our results demonstrate that serum phosphorus and Ca×Pi product are positively correlated with LVMI and negatively correlated with LVEF.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…LVH is generally considered to be associated with hypertension caused by uremia [3]. Nevertheless, our results demonstrate that serum phosphorus and Ca×Pi product are positively correlated with LVMI and negatively correlated with LVEF.…”
Section: Discussionmentioning
confidence: 48%
“…Patients with CKD carry a 10–20 times higher cardiovascular disease (CVD) mortality than that in the general population [2]. CVD is the leading cause of mortality in CKD patients [3]. However, the pathogenesis of cardiovascular injury in ESRD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic kidney disease (CKD) are at high risk of developing cardiovascular disease (CVD) [1,2]. Longitudinal studies have established that CVD events occur more frequently than renal events in CKD, and CVD mortality rates are in fact higher than the rates of reaching end-stage renal disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the benefit of controlling hypertension in dialysis patients [21,22,23,24,25,26]. However, hypertension control is difficult in the general population and hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%